Effects of the generated functional groups by PECVD on adhesiveness of adipose derived mesenchymal stem cells - Kwon, Sungyool; Ban, Wonjin; Lim, Hyuna; Seo, Youngsik; Park, Heonyong; Kim, Eun Joo; Cho, Yong Ki; Park, Sang Gyu; Jung, Donggeun (Journal of Vacuum Science and Technology A: Vacuum, Surfaces and Films, 2018)
Plasma techniques extending into bio-applications have attracted much attention from researchers studying biomaterials and tissue engineering. Since the biocompatibility of culture dishes depends on the physicochemical properties of the surface and the cultured cell type, plasma techniques to appropriately modify these properties are useful for cell culture. In this study, the authors attempted to fabricate a culture dish that exhibits optimal surface properties for the culture of adipose-derived mesenchymal stem cells (ADMSCs). For this purpose, the authors modified polystyrene culture dishes using a plasma-enhanced chemical vapor deposition system that forms various chemical functional groups on the dishes. The modified culture dishes were fabricated using three methods, which were argon/hydrogen plasma surface treatment and functional film deposition from either pyrrole or acetylene precursors. ADMSC adhesion was dramatically enhanced on the culture dishes deposited with pyrrole precursors. The authors optimized the process condition of pyrrole deposition to improve ADMSC adhesion by varying the plasma power from 100 to 900 V. The strongest ADMSC adhesion was shown with a plasma power of 900 V. ADMSC adhesion was improved with higher amounts of nitrogen-related functional groups such as imine, amide, and amine groups. In conclusion, pyrrole deposition on culture dishes is an effective method to promote the growth of ADMSCs and will be a useful technique for enhancing the biocompatibility of polystyrene materials in stem cell engineering.
Keywords: Adipose-derived mesenchymal stem cells; Chemical functional groups; Functional films; Physicochemical property; Plasma enhanced chemical vapor deposition systems; Plasma surface treatment; Plasma techniques; Process condition